Упростите выражение 2+6p/p умножить (1/2-6p+1/27p^3-1 делить 1+3p/1+3p+9p^2)(решите пожалуйста очень надо)
Упростите выражение
2+6p/p умножить (1/2-6p+1/27p^3-1 делить 1+3p/1+3p+9p^2)
(решите пожалуйста очень надо)
Ответ(ы) на вопрос:
[latex] \frac{2+6p}{p} * \frac{0.5p-6}{27 p^{3}-1 } : \frac{1+3p}{1+3p+9 p^{2} } [/latex] =
= [latex] \frac{2+6p}{p} * \frac{0.5-6p}{27 p^{3}-1}* \frac{1+3p+9 p^{2} }{1+3p} [/latex] =
= [latex] \frac{2(1+3p)}{p} * \frac{0.5-6p}{(3p-1)(1+3p+9 p^{2} )} * \frac{1+3p+9 p^{2} }{1+3p} [/latex] =
= [latex] \frac{1-12p}{3 p^{2}-p } [/latex]
Не нашли ответ?
Похожие вопросы